The effect of nanoscale biodegradable polymer film on the healing of cut wounds of the skin of complicated Psevdomonas auregenosa (Experimental research) - O. Y. Popadyuk; S. M. Genyk; R. V. Kuzyk; V. V. Kostyuk (Сучасні медичні технології)
Introduction. Effect of the biodegradable polymer film saturated with zinc nanoxide and hydrated C60 fullerene on the healing of skin cut wounds complicated Pseudomonas aeruginosa are study.